TRANSFORMATION OF LABOR ORGANIZATION IN THE BANKING SECTOR THROUGH THE INTEGRATION OF ARTIFICIAL INTELLIGENCE - Yusupova M.A. (Labor economics and human capital, 2024)
The article examines the transformation of labor organization in the banking sector through the integration of artificial intelligence (AI). Digital labor organization involves the automation of routine tasks, the use of AI for data analysis and decision-making, and the creation of new forms of customer interaction. The integration of AI requires a review of existing workflows, the training of employees in new skills, and consideration of legal and ethical aspects. The article analyzes approaches to digital labor organization in commercial banks of Uzbekistan, including integrative, multidisciplinary, comprehensive, and innovative approaches. Strategies for creating balanced reward systems for attracting and retaining employees in the context of digital transformation are also discussed.